Well-Dispersed Silica Fume by Surface Modification and the Control of Cement Hydration - Rui Ma; Liping Guo; Wei Sun; Zhidan Rong (Advances in Civil Engineering)
Silica fume (SF) is a valuable nanoscaled industrial by-product used in cementitious materials owing to its filling and pozzolanic effect. However, the heavy agglomeration of SF is a severe and common problem. In this study, surface modification with polyacrylic acid (PAA) was applied on SF to achieve a better dispersion and to optimize the hydration process of cement at early age. The particle size distribution and surface properties of SF, as well as the cement hydration with modified SF, were investigated. The results demonstrated that the agglomeration of SF particles was efficiently mitigated by the surface treatment with PAA, and the acceleration effect of SF was delayed by the resistance of the surface layer at early age. However, the grafted PAA layer eventually dropped in alkali solution after 6 hours, and the hydration rate was increased again and continued for long time. This work indicated that surface-modified SF was well dispersed and was able to regulate the hydration rate of cement.